2005
DOI: 10.1007/s00210-005-1075-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of protection by pantoprazole against NSAID-induced gastric mucosal damage

Abstract: The use of nonsteroidal anti-inflammatory drugs (NSAIDs) can be associated with severe adverse digestive effects. In clinical settings, proton pump inhibitors have proven to be effective in preventing and healing NSAID-induced gastroduodenal lesions. The present study investigates the mechanisms of protection afforded by pantoprazole against gastric injury induced by different NSAIDs in rats. Animals were orally treated with indomethacin (100 micromol/kg), diclofenac (60 micromol/kg), piroxicam (150 micromol/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 48 publications
4
45
0
1
Order By: Relevance
“…Moreover, rats treated with the combination of ranitidine and diclofenac showed decreased production of gastric acid and also decreased incidence of gastric ulcers. This may be attributed to the ranitidine's antioxidative potential as has been reported in previous studies (7,20,23) . Histologically too, ranitidine was observed to reduce gastric and liver damage which may be due to inhibition of neutrophil activation as observed in earlier studies (21,22) .…”
Section: • Change In Phsupporting
confidence: 74%
See 1 more Smart Citation
“…Moreover, rats treated with the combination of ranitidine and diclofenac showed decreased production of gastric acid and also decreased incidence of gastric ulcers. This may be attributed to the ranitidine's antioxidative potential as has been reported in previous studies (7,20,23) . Histologically too, ranitidine was observed to reduce gastric and liver damage which may be due to inhibition of neutrophil activation as observed in earlier studies (21,22) .…”
Section: • Change In Phsupporting
confidence: 74%
“…Previous studies have reported that NSAIDs may also induce gastric damage by acid-independent mechanisms such as by increasing oxidative stress parameters viz. increase in mucosal myeloperoxidase levels, together with increase in mucosal malondialdehyde and reduced glutathione concentration (7,20,23) . Malondialdehyde is an end product of the peroxidation of polyunsaturated fatty acids and related esters within cell membranes, such that the measurement of this compound represents a suitable index of oxidative tissue damage (15) .…”
Section: • Change In Phmentioning
confidence: 98%
“…PPIs have a gastroprotective effect, independent on their antisecretory actions [73], which is probably mediated by inhibition of neutrophil functions as well as antioxidant actions [74]. The effect of PPIs on HO-1 induction remain controversial; Becker et al [75] showed that both Omeprazole and Lansoprazole strongly induce HO-1 expression in gastric epithelial cells in vitro, while Takagi et al [76] mentioned that Omeprazole weakly induces the expression of HO-1 in gastric epithelial cell lines.…”
Section: Kotob Et Almentioning
confidence: 99%
“…Omeprazole, pantoprazole and lansoprazole are widely used as clinical treatments for gastric and duodenal ulcers (27,28). Administration of lansoprazole prevents gastric mucosal injury by indomethacin, piroxicam or ketoprofen by reducing cyclooxygenase-2 (COX-2) mRNA expression in SD rats (29).…”
Section: Anti-ulcer Property Of Camellia Oilmentioning
confidence: 99%